Gut Microbiota as the Link between Elevated BCAA Serum Levels and Insulin Resistance - Gojda, Jan; Cahova, Monika (Biomolecules, 2021)
The microbiota-harboring human gut is an exquisitely active ecosystem that has evolved in a constant symbiosis with the human host. It produces numerous compounds depending on its metabolic capacity and substrates availability. Diet is the major source of the substrates that are metabolized to end-products, further serving as signal molecules in the microbiota-host cross-talk. Among these signal molecules, branched-chain amino acids (BCAAs) has gained significant scientific attention. BCAAs are abundant in animal-based dietary sources; they are both produced and degraded by gut microbiota and the host circulating levels are associated with the risk of type 2 diabetes. This review aims to summarize the current knowledge on the complex relationship between gut microbiota and its functional capacity to handle BCAAs as well as the host BCAA metabolism in insulin resistance development. Targeting gut microbiota BCAA metabolism with a dietary modulation could represent a promising approach in the prevention and treatment of insulin resistance related states, such as obesity and diabetes.
Keywords: symbióza; Insulin Resistance; inzulinová rezistence; Obesity; type 2 diabetes; gut microbiome; větvené aminokyseliny; branched-chain amino acids; krevní glukóza; obezita; Amino Acids, Branched-Chain; Diabetes Mellitus, Type 2; Gastrointestinal Microbiome; diabetes mellitus 2. typu; střevní mikroflóra; insulin resistance; lidé; Humans; gut metabolome; Symbiosis; Blood Glucose